Diagnostic Methods for the Comprehensive Health Assessment of the Long-Spined Sea Urchin, Diadema antillarum - Ruth Francis-Floyd (EDIS, 2020)
This 55-page document contains a wealth of information on the long-spined sea urchin, which is an important animal in coral reef ecosystems. The publication discusses diagnostic methods for Diadema antillarum and provides reporting forms for laboratory and diagnostic work. Written by Ruth Francis-Floyd, Jan Landsberg, Roy Yanong, Yasu Kiryu, Shirley Baker, Deborah Pouder, William Sharp, Gabriel Delgado, Nicole Stacy, Tom Waltzek, Heather Walden, Roxanna Smolowitz, and Greg Beck, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, May 2020.